Diversity of diurnal butterflies (Lepidoptera: Papilionoidea and Hesperioidea) in Santiago de Cali, Valle del Cauca, Colombia - RAMÍREZ-RESTREPO, LORENA; CHACÓN DE ULLOA, PATRICIA; CONSTANTINO, LUÍS MIGUEL (Revista Colombiana de Entomología, 2007)
Between March and August 2005, diurnal butterflies were sampled with aerial nets and Van Someren-Rydon traps, in six urban zones and one suburban zone that cover approximately 210 ha of the municipality Santiago de Cali, in the department Valle del Cauca. The inventory recorded 193 species grouped in five families, Nymphalidae being the family with the greatest richness (72 species), followed by Hesperiidae (67), Lycaenidae (28), Pieridae (19) and Papilionidae (seven). The mean richness was 70.9 ± 24.4 species, with a maximum value at the Ecoparque del Río Pance (124), located in the suburban zone south of the city, and a minimum of 50 species at the Parque del Amor, the locality closest to the city’s industrial zone. Richness and species composition are compared among the sampled green zones. To encourage the presence of these insects in the urban zone, concrete actions are proposed such as growing food plants for larvae and adults, and the establishment of permanent humidity sources.